Monocular Versus Binocular Calibrations in Evaluating Fixation Disparity With a Video-Based Eye-Tracker. (August 2015) - Švede, Aiga; Treija, Elīna; Jaschinski, Wolfgang; Krūmiņa, Gunta
When measuring fixation disparity (an oculomotor vergence error), the question arises as to whether a monocular or binocular calibration is more precise and physiologically more appropriate. In monocular calibrations, a single eye fixates on a calibration target that is taken as having been projected onto the center of the fovea; the corresponding vergence state represents the heterophoria (the resting vergence position), which has no effect on the calibration procedure. In binocular calibrations, a vergence error may be present and may affect the subsequent measurement of the fixation disparity during binocular recordings. This study includes a test of the precision of both monocular and binocular calibrations and an evaluation of the impact of the calibration procedure on the measurement of fixation disparity during a dot scanning task. Our results show that 11 participants (out of 19) each exhibited a significant difference in fixation disparity with the two types of calibration procedures. In addition, the fixation disparity was more strongly affected by heterophoria undergoing monocular calibration, as opposed to binocular calibration. This serves as additional evidence showing that the monocular calibration produces a physiologically more plausible fixation disparity and seems to be more appropriate for studying the full extent of fixation disparity.